Voting power derives from the poll distribution: Shedding light on contentious issues of weighted votes and the constitutional treaty - Iain Paterson (Institute for Advanced Studies (IHS), 2006)
Analysis of the Constitutional Treaty of the European Union shows that there is a serious discrepancy between the voting power gradient of Member States computed by the Shapley-Shubik and Banzhaf indices. Given the lack of compelling arguments to choose between these indices on purely axiomatic grounds, we turn to a probabilistic approach as pioneered by Straffin (1977) focusing on the probability distribution of voting poll outcomes. We present a unifying model of power indices as expected decisiveness, which shows that the defining feature of each approach is a particular distribution of the voting poll. Empirical evidence drawn from voting situations, in addition to a consideration of first principles, leads us to reject one of these approaches. The unified formulation allows us to develop useful related concepts of efficiency and blocking leverage, previously used solely by a 'Banzhaf' approach, for the case of Shapley-Shubik, and a comparison of results is shown.
Keywords: C43; C71; D02; D71; D81; 330; voting power indices; power gradient; coefficient of representation; expected decisiveness; efficiency; blocking leverage; Constitution of the European Union; Wahl; Macht; Index; Verfassung; Theorie; EU-Staaten